Pengaruh Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. Bima Sakti Logistik Di Jakarta Timur - Zahra Arita Putri; Sudiarto Sudiarto (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study was to determine the effect of leadership and work motivation on employee performance at PT. Bima Sakti Logistik in East Jakarta. The method used is quantitative with an associative approach. The sampling technique used saturated sampling, namely 58 respondents. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients and hypothesis tests. The results of this study are Leadership has a significant effect on employee performance with the regression equation Y = 34.389 + 0.409X₁, obtained a determination coefficient value of 18.7% and the hypothesis test obtained a calculated t value> t table or (3.591> 1.672). Work Motivation has a significant effect on employee performance obtained by the regression equation Y = 25.929 + 0.566X₂, obtained a determination coefficient value of 27.8% and the hypothesis test obtained a calculated t value> t table or (4.641> 1.672). Leadership and work motivation simultaneously significantly influence employee performance, as shown in the regression equation Y = 12.301 + 309X₁ + 0.483X₂. The coefficient of determination, or contribution of the simultaneous influence, is 37.9%. Hypothesis testing yields a calculated F value > F table, or (16.753 > 3.165)..